Coping strategies and mental reliability as psychological determinants of success in sport - Rogaleva, L.; Sekrecova, Z.; Khon, N.; Malkin, V.; Kim, A. (Advances in Social Science, Education and Humanities Research, 2019)
Sport is a popular activity for young people. At the same time, they are often not psychologically ready to overcome the difficulties of sports activities. The purpose of the study is to identify the optimal coping strategies of athletes who ensure success in sports and to identify the features of psychological reliability among athletes of different skill levels. 60 student-athletes involved in various sports (climbing, judo, athletics, team sports, etc.) participated. The first group included athletes of the first category (27 people), and the second group of candidates for the master of sports (33 people). The study proved that coping strategies and mental reliability are closely related to the level of sportsmanship. Higher-level athletes (candidates and masters of sports) demonstrate more active coping strategies and have a higher level of competitive emotional stability. The data obtained must be taken into account when conducting psychological work with athletes and further research may be devoted to the study of conditions that ensure the formation of more adequate behavioral strategies for athletes that provide a higher level of their sportsmanship.